Covalently Sandwiching MXene by Conjugated Microporous Polymers with Excellent Stability for Supercapacitors. Issue 10 (2nd September 2020) - Yang, Weizu; Huang, Bingyu; Li, Longbin; Zhang, Kaiyang; Li, Yizhe; Huang, Jun; Tang, Xiannong; Hu, Ting; Yuan, Kai; Chen, Yiwang
Abstract: 2D MXenes have attracted wide attention due to their unique chemical and physical properties. However, MXene nanosheets suffer from restacking and are susceptible to oxidation and consequently lose their functional properties which limits their applications. Thus, it is desirable to explore strategies to preserve MXene nanosheets and avoid oxidation. Herein, an effective strategy to produce MXene‐based conjugated microporous polymers (M‐CMPs) by covalently sandwiching MXene between CMPs using p‐iodophenyl functionalized MXene as templates is demonstrated. The as‐prepared M‐CMPs inherit the 2D architecture and high conductivity of MXene in terms of hierarchical porous structure and large specific surface area of CMPs. Moreover, the restacking and oxidation of MXene are simultaneously suppressed. Such advanced structural merits are critical for electrochemical energy storage. As‐proof‐of‐concept, the M‐CMPs are used as electrode materials for supercapacitors. As expected, with the improved structural advantages, M‐CMPs showcase superior capacitive performance than the MXene and CMPs counterparts. This work not only provides an opportunity for fabricating high performance MXene nanocomposites for energy storage/conversion but also has the potential to be generalized to resolve the challenges in the area of MXene engineering. Abstract : The restacking and oxidation of MXene nanosheets are simultaneously suppressed by covalently sandwiching MXene between conjugated microporous polymers. This strategy not only provides an opportunity for resolving the challenges in the area of MXene engineering but also has the potential to fabricate high performance MXene‐based nanocomposites for energy storage/conversion.